(untitled) (Global Journal of Human-Social Science, 2016)
Globalization has compressed the world to what is now called a global village The phenomenal increase in the production of goods and services and the rapid movement of persons across national boundaries have reduced the exclusivity of national frontiers Thus the growing interconnectivity has spawned what may be described as a global consciousness and culture Therefore the rise of NGOs is a precipitate of this global transformation NGOs which were hitherto an exclusive preserve of some regions have come to assume a global character It is now located in almost all the corners of the world This paper seeks to examine the problems and prospects associated with this development in the Third World particularly Africa In looking at the problems our data collection method was based on two sources Primary and Secondary sources The primary sources include personal interviews and discussions while the secondary sources include literature review examination of official bulletins gazettes newspapers and magazines It was discovered that NGOs in Africa perform some vital functions in the continent because of its underdeveloped character These functions were obviously neglected by the state and the local authorities We therefore suggest that the state need not suffocate NGOs or be wary about of their emergence Rather they should have a synergistic relationship through networking and partnership based on best practices and standard of accountability